Penerapan Kompres Jahe (Zingiber Officinale) terhadap Penurunan Nyeri pada Lansia dengan Asam Urat - Diah Ayu Saputri; Vincencius Surani; Sri Indaryati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Uric acid levels exceeding the normal range can lead to various clinical manifestations, such as joint pain and stiffness, tingling sensations, and swelling and erythema resulting from inflammation. Patients may also experience prolonged fatigue, general discomfort, and urinary disturbances; in some cases, acute attacks may be accompanied by an elevated body temperature or fever. A warm ginger compress is a traditional remedy or alternative therapy that combines heat application with ginger to alleviate pain. Objective: To implement an evidence-based nursing intervention for elderly patients suffering from joint pain due to high uric acid levels. Methods: This study employed a case study design involving the administration of ginger compresses within a nursing care framework. Three respondents participated in the study; the intervention was administered once daily for three days—from June 20, 2026, to June 22, 2026—at Bhayangkara Mohammad Hasan Hospital in Palembang, South Sumatra. Results: Following the three-day application of the evidence-based ginger compress intervention, the nursing issues of acute pain, impaired comfort, and knowledge deficit were successfully resolved at Bhayangkara Mohammad Hasan Hospital. Recommendations: It is hoped that the implementation of this evidence-based practice will contribute to the body of knowledge and provide further information regarding the use of ginger compresses to reduce joint pain associated with high uric acid levels in the elderly.